PENGARUH GAYA HIDUP, PENDAPATAN DAN SELERA KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PADA USAHA KULINER ASING - rukaiyah, siti (Dinamis : Journal of Islamic Management and Bussiness, 2023)
This research aims to analyze the partial influence of lifestyle on purchasing decisions in foreign culinary businesses, the partial influence of income on purchasing decisions in foreign culinary businesses, the partial influence of consumer preferences on purchasing decisions in foreign culinary businesses, and the simultaneous influence of lifestyle, income, and consumer preferences on purchasing decisions in foreign culinary businesses. This research is quantitative, employing Proportionate Stratified Random Sampling for sample collection, resulting in a sample size of 393 individuals. Data were collected through observation and questionnaires distributed to respondents. The analytical techniques used include descriptive statistical analysis and a binary logistic regression model, which encompasses multicollinearity tests, simultaneous tests (omnibus test of model coefficients), individual tests (Wald test), model fit tests (Hosmer and Lemeshow test), model interpretation, model classification accuracy, and the determination coefficient test (Nagelkerke R Square). The results of this study indicate that Lifestyle (X1) and Consumer Preferences (X3) have a significant partial influence on Purchasing Decisions (Y), while Income (X2) does not have a partial influence on Purchasing Decisions (Y). The simultaneous influence of Lifestyle, Income, and Consumer Preferences directly affecting Purchasing Decisions is 38.4%.